The New Education Fellowship, the Progressive Education Association, and the US Department of State: South America as part of a complex entanglement. - Silva Rabelo, Rafaela (Paedagogica Historica, 2021)
In 1943, a report sent to the executive board of the New Education Fellowship (NEF) informed the board that, during a trip to South America in 1942, Carleton Washburne had formed sections in Colombia, Ecuador, Chile, Paraguay, and Brazil on the NEF's behalf. In some publications, Washburne mentions that it was a study trip commissioned by the US Department of State but does not refer to the NEF. These documents lead to different narratives when analysed separately, but they reveal unexpected connections when confronted together. In 1941, the NEF's Eighth International Conference was held in the USA in Ann Arbor, Michigan. The conference in the USA was a unique opportunity to strengthen the bonds with Latin American countries that, until that moment, had barely participated in NEF activities. However, the conference also coincided with the US political agenda related to the Good Neighbour policy. Some months later, Washburne started his trip to South America, which was commissioned by the Division of Cultural Relations, a division of the US Department of State. Between April and September 1942, he visited schools, met political authorities and renowned educators, and delivered lectures on the New Education. Based on Washburne's trip to South America, the following article explores how the New Education Fellowship, Progressive Education Association, and US Department of State were intertwined. Thus, using the vestiges and traces left in different documents such as correspondence, reports, magazines and newspapers, I explore the notion of networks while turning the scales of analysis towards a connected history.